The World Central Kitchen cookbook : feeding humanity, feeding hope - Andrés, José, 1969-; Chapple-Sokol, Sam (Clarkson Potter/Publishers, 2023)
A captivating collection of stories and recipes from renowned chefs, local cooks, and celebrity friends of José Andrés's beloved nonprofit World Central Kitchen (WCK), which feeds communities impacted by natural disasters and humanitarian crises; with a foreword from Stephen Colbert.